2016
DOI: 10.1002/ana.24818
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography–based quantification of lesion water uptake identifies patients within 4.5 hours of stroke onset: A multicenter observational study

Abstract: Quantification of brain water uptake identifies stroke patients with symptom onset within 4.5 hours with high accuracy and may guide the decision to use thrombolysis in patients with unknown time of stroke onset. Ann Neurol 2016;80:924-934.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
148
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(153 citation statements)
references
References 25 publications
5
148
0
Order By: Relevance
“…Consequently, the use of NCCT is intrinsically a quantitative and standardized process for infarct brain tissues. The previous literature suggested that since inherent anatomical structures in the human brain are symmetric, ischemic tissues can be highlighted by comparing the left and right sides of a brain [18,19].…”
Section: Asymmetric Interpretationmentioning
confidence: 99%
“…Consequently, the use of NCCT is intrinsically a quantitative and standardized process for infarct brain tissues. The previous literature suggested that since inherent anatomical structures in the human brain are symmetric, ischemic tissues can be highlighted by comparing the left and right sides of a brain [18,19].…”
Section: Asymmetric Interpretationmentioning
confidence: 99%
“…Furthermore, data from primate stroke show that water uptake by white matter (WM) is less severe than that by gray matter (GM) 2 . Taking into account the water data above and the fact that the ischaemic core is effectively without blood supply, it is difficult to appreciate the water uptake values reported by Minnerup et al 1 . One potential reason for high water uptake estimate by Minnerup et al 1 could be the use of aqueous HU calibration instead of measurements of HUs against water content in the brain tissue 4 .…”
Section: Computed Tomography-based Acute Stroke Lesion Timing and Patmentioning
confidence: 99%
“…Minnerup and co-workers proposed a computed tomography (CT) -based procedure to determine age of acute/hyperacute stroke to aid patient stratification for reperfusion therapy 1 . The CT procedure converts Hounsfield Units (HU) determined in the stroke lesion into net water uptake due to ischaemia.…”
Section: Computed Tomography-based Acute Stroke Lesion Timing and Patmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated optimal threshold for procalcitonin in this analysis was 1.2 ng/ml. Such an approach to the problem of multiple diagnostic thresholds appears to be a most promising initiative and has been implemented in at least one independent study [31]. …”
mentioning
confidence: 99%